Evaluating Guru Penggerak Training Program's Impact Using Kirkpatrick Level 4 Model: A Data-Driven Analysis with Python Visualization - Utami, Ajeng Astri; Laihad, Griet Helena; Karmila, Nita (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to evaluate the outcomes (Level 4) of the Kirkpatrick Model in the implementation of the Guru Penggerak Program in Bogor City State High School/Vocational School. Using a qualitative approach with an evaluative method, data were obtained through documentation studies and interviews with 14 school principals selected via purposive sampling. Data analysis followed Miles and Huberman's interactive model, consisting of three stages: data reduction, data presentation, and conclusion drawing. Theme frequencies were analyzed and visualized using Python and pandas. This study shows that the Guru Penggerak Program has a varied impact on schools, with the most dominant impact seen on improving student learning outcomes, although the effect is not even at the institutional level. Based on correlation analysis and documentation studies, the impact of programs on schools shows a complex relationship. The correlation of -0.65 between the learning community and the role of the principal and -0.41 between the role of the principal and the learning outcome indicated a lack of managerial support. A correlation of 0.00 between community learning and learning outcomes and 0.11 between community learning and positive impact on school indicates that the impact of the program is limited without structural support. A correlation of -0.54 between student learning outcomes and positive impacts on schools shows an unequal impact, while a correlation of 0.47 between the role of principals and positive impacts on schools confirms the importance of the role of leadership in creating a climate that supports change.